Effect of Ag additions on the β phase formation reaction in the Cu-9 wt.%Al-6 wt.%Mn alloy - Adorno, A. T. [UNESP]; Carvalho, T. M. [UNESP]; Silva, R. A G; Santos, C. M A [UNESP]; Magdalena, A. G. [UNESP] (Elsevier, 2015)
The influence of 4 and 5 wt.%Ag additions on the kinetics of β [T7-(CuMn)3Al] phase formation reaction in the Cu-9 wt.%Al-6 wt.%Mn alloy was studied using differential scanning calorimetry (DSC), X-ray diffractometry (XRD) and scanning electron microscopy (SEM). The results indicate that the conversion dependence of the activation energy has a descending shape, suggesting a multi-step process involving reversible reactions. The presence of Ag facilitates the formation of the β phase. The results also showed that the Ag precipitates formation includes the dissolution of Mn and Al atoms, thus decreasing the partial fraction of these elements available to react.
Keywords: Kinetics; Metals and alloys; Solid state reactions; Thermal analysis